Preparation of copper-chelate quaternized carboxymethyl chitosan/organic rectorite nanocomposites for algae inhibition. (20th October 2016) - Cai, Jihai; Ye, Weijie; Wang, Xiaoying; Lin, Wensheng; Lin, Qixuan; Zhang, Qiang; Wu, Fangchengyuan
Highlights: A new type of environmentally friendly algae inhibiting agent were prepared. The thermostability and algae inhibiting advantages of QCMC, OREC and Cu 2+ were combined. QCMC/OREC-Cu nanocomposites showed high thermal stability. QCMC/OREC-Cu nanocomposites exhibited excellent algae inhibition activity. Abstract: Quaternized carboxymethyl chitosan/organic rectorite (QCMC/OREC) nanocomposites were rapidly prepared by intercalating QCMC into the layer of OREC under microwave irradiation. And then copper-chelate QCMC/OREC (QCMC/OREC-Cu) nanocomposites were obtained by mixing QCMC/OREC with CuSO4 solution. XRD and TEM results indicated that QCMC/OREC nanocomposites were obtained and QCMC was dispersed in the interlayer of OREC. Besides, FT-IR results revealed that the hydrogen bonds and electrostatic interaction in QCMC/OREC-Cu were both stronger than those in QCMC/OREC because of introducing the Cu 2+ . The thermogravimetric analysis showed that the thermal stability of QCMC/OREC-Cu nanocomposites was higher than QCMC and QCMC/OREC. Algae inhibition assay revealed that QCMC/OREC-Cu nanocomposites had stronger antifouling activity than original QCMC and QCMC/OREC. This work provides important basis for developing novel antifouling materials.